Breeding and methodology in forage shrubs - Stringi L.; Accardo A.; Giambalvo D. (Fodder trees and shrubs, 1994)
An overall analysis of the state of art of breeding and methodology in shrubs was carried out. First of all the review focuses on the breeding systems and it outlines the importance of improving knowledge on the latter for breeding shrubby species; moreover, a rapid, adoptable methodology is indicated for indirect determination of the breeding systems and the classification of various genotypes. Afterwards, the poor development of the breeding plans in shrubs is underlined; previsions of their improvement in relation to research trends are reported and the adoptable breeding plans are indicated on the basis of up to date knowledge and of the poor economical importance generally attributed to shrubby species. The analysis continues on selection, which is unanimously considered as the prevalent expression of breeding activity in shrubs. On these aspects regarding forage shrubs, the review outlines the difficulties involved in terms of time, costs and efficiency; thus a synthesis of the methods used today for the estimation of biomass, which are suitable for selecting among different populations and within a single population, is reported; furthermore for each of these methods, the techniques and the level of accuracy and of suitability are indicated. Criteria and methods used in selection for improving palatability are pointed out, outlining the importance of taking into consideration grazing animals for selection, the type approach for their management and the limits of the main selection methods used today. Thereafter, basic criteria of selection for tolerance to salinity are analysed and the possibilities of using modern technologies for selection in controlled environments are indicated. At last a critical, conclusive evaluation of the aspects analysed is done and the opportunity of developing new, known technologies for a faster improvement of shrubs is expressed.
ECC-CAMAR 800-CT90-0021 Research Project Meeting on Fodder Trees and Shrubs, 1992/10/12-13, Palermo (Italy)